Analysis of Language Textbooks in Georgia: Approaches to Gender Equality of Males and Females While Teaching Languages. Issue 2 (April 2023) - Tabatadze, Shalva; Gorgadze, Natia
This study aimed to explore gender equality in language textbooks in Georgian schools. The content analysis method was used to answer the research questions, and a theoretical framework was developed based on Porreca's Analytical Framework (1984). The research revealed that men remain more visible in textbooks. Social roles, activities, and professions are gender-biased, and the books contribute to the development of gender stereotypes. The study identified five different approaches that school textbook authors adopt toward gender equality: (1) superficial, (2) artificial, (3) additive, (4) deliberate ignorance, and (5) attitudinal nondeliberate gender mainstreaming approach.